Hubungan Antara Pertumbuhan Ekonomi dan Ketimpangan Pendapatan di Provinsi Nusa Tenggara Barat (Pembuktian Hipotesis Kuznets) - Baiq Wihan Sirtama (Jurnal Ilmu Ekonomi, 2021)
This study aims to determine the level of income inequality, the relationship between Economic Growth and Income Inequality, and the Kuznets Hypothesis. The method used is the Williamson Index, Theil Entropy Index, Pearson Correlation, and the Kuznets Hypothesis. The results obtained from the Williamson Index and Theil Entropy Indeks between districts/cities in the Province of NusaiSoutheastern West 2001-2020 show a trim income inequality level with values ​​of 0.22 and 0.02. The results obtained from the Pearson Correlation between Regencies/Citiesiin West Nusa Tenggara Province in 2001-2020 showed a relationship. Still, it was less intense because it was at 0.257 and 0.303. The results obtained from the visual analysis illustrate the relationship between Economic Growth and Income Inequality, forming an inverted U, which means that in the early period of economic growth, there was an increase in income inequality, as evidenced by the continued growth of economic growth from 2001 to 2010 but was followed by the rise in income inequality—rising income inequality. Then, in the next period, namely in 2011 to 2020, economic growth continued to grow but was followed by a decrease in income inequality, meaning that the Kuznets Hypothesis turned out to be valid in the Province of West Nusa Tenggara in 2001-2020.